2004
DOI: 10.1029/2003je002160
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of near‐surface hydrogen on Mars

Abstract: [1] Neutron data observed using the Neutron Spectrometer aboard 2001 Mars Odyssey provide a lower limit to the global inventory of Martian water-equivalent hydrogen. Hydrogen-rich deposits ranging between about 20% and 100% water-equivalent by mass are found poleward of ±50°latitude, and less rich, but significant, deposits are found at near-equatorial latitudes. The equatorial deposits between ±45°latitude range between 2% and 10% water-equivalent hydrogen by mass and reach their maximum in two regions that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
333
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(364 citation statements)
references
References 46 publications
28
333
0
3
Order By: Relevance
“…Larger polygons, however, are also formed in material with lower ice content (Lachenbruch, 1966) as was discussed for the terrestrial polygons (Table 1). No clear relationship between polygon dimension and ground-ice content, which increases with latitude (e.g., Feldman et al, 2004), could be observed on Mars (Mangold et al, 2004;Mangold, 2005;Levy et al, 2009a). The size of the upland polygons (UP1) is consistent with the findings of the Gamma Ray Spectrometer (GRS) that only~4 tõ 10 wt.% water-ice equivalent exists currently in the upper surface layer (b1 m depth) in the regions between 45°S and 45°N Mitrofanov et al, 2002;Feldman et al, 2004).…”
Section: Genesis Of Mars Polygons and Environmental Implicationssupporting
confidence: 72%
See 1 more Smart Citation
“…Larger polygons, however, are also formed in material with lower ice content (Lachenbruch, 1966) as was discussed for the terrestrial polygons (Table 1). No clear relationship between polygon dimension and ground-ice content, which increases with latitude (e.g., Feldman et al, 2004), could be observed on Mars (Mangold et al, 2004;Mangold, 2005;Levy et al, 2009a). The size of the upland polygons (UP1) is consistent with the findings of the Gamma Ray Spectrometer (GRS) that only~4 tõ 10 wt.% water-ice equivalent exists currently in the upper surface layer (b1 m depth) in the regions between 45°S and 45°N Mitrofanov et al, 2002;Feldman et al, 2004).…”
Section: Genesis Of Mars Polygons and Environmental Implicationssupporting
confidence: 72%
“…No clear relationship between polygon dimension and ground-ice content, which increases with latitude (e.g., Feldman et al, 2004), could be observed on Mars (Mangold et al, 2004;Mangold, 2005;Levy et al, 2009a). The size of the upland polygons (UP1) is consistent with the findings of the Gamma Ray Spectrometer (GRS) that only~4 tõ 10 wt.% water-ice equivalent exists currently in the upper surface layer (b1 m depth) in the regions between 45°S and 45°N Mitrofanov et al, 2002;Feldman et al, 2004). If higher ground-ice contents than in the upper layer occur deeper than 1 m, which was inferred from the dimension of the scalloped depressions (Morgenstern et al, 2007;Ulrich et al, 2010), seasonal thermal waves should not reach this depth at the present time (Mellon, 1997;Mangold et al, 2004).…”
Section: Genesis Of Mars Polygons and Environmental Implicationsmentioning
confidence: 99%
“…Gamma Ray Spectrometer and Neutron Spectrometer (GRS/NS) observations of regolith at latitudes N50-60°show substantial amounts of water ice within a few tens of centimeters of the surface (Boynton et al, 2002;Feldman et al, 2004). The soils may therefore have had a degree of cohesion from ice cement holding the grains together, resulting in little mobile sediment available for transport by the wind.…”
Section: Sediment Source and Spatial Distributionmentioning
confidence: 99%
“…3,4 These discoveries have reignited the concept of making methane on Mars for propulsion with oxygen. Previously, the biggest drawback to the methane option was the need to bring hydrogen from Earth, which is difficult to store and transport due to its low density and liquefaction temperature.…”
Section: Introductionmentioning
confidence: 99%